The impacts of the “4+7” pilot policy on the volume, expenditures, and daily cost of Serotonin-Specific Reuptake Inhibitors (SSRIs) antidepressants: A quasi-experimental study - Wen, Xiaotong; Wang, Zhaolun; Xu, Luxinyi; Luo, Jia; Geng, Xin; Chen, Xiaoze; Yang, Ying; Cui, Dan; Mao, Zongfu (Frontiers in Pharmacology, 2022)
Abstract Objectives: The purpose of this study was to quantitatively evaluate the impacts of the“"4+7” pilot policy on purchase volume, purchase expenditures, and daily cost and to find the changes in the use of SSRIs. Methods: Data was collected covering a 31-month period, before, during, and after the “4+7” pilot policy was implemented in Shenzhen. Interrupted time-series analysis (ITSA) was used to examine whether there had been a significant effect with the onset of the “4+7” pilot policy in March 2019. Findings: The DDDc of policy-related drugs had a substantial drop of 2.93 yuan under the “4+7” pilot policy. The result has shown a 76.70% increase in volume and a 3.39% decrease in the expenditure of policy-related drugs. This study found that the “4+7” pilot policy resulted in an increase in the proportion of purchasing winning drugs, with an increment of 85.60 percent. After the implementation of the “4+7” pilot policy, policy-related drugs decreased by 443.55thousand CNY. The study indicated that DDDs of winning products significantly increase as shown in the regression with level coefficient (β2) of -224.17 (p < 0.001) and trend coefficient (β3) of 15.74 (p<0.001). The result revealed that that both DDDs and expenditures of branded products showed a significant decrease in the regression in the post-intervention period (level coefficient of DDDs: β2=-57.65, p<0.01, trend coefficient of DDDs: β3=-3.44, p<0.01; level coefficient of expenditure: β2=-712.98, p<0.01, trend coefficient of expenditure: β3=-40.10, p<0.01). Conclusion: The volume-based procurement has successfully led to price reductions and improved affordability of medicines, especially for those with chronic diseases. The volume-based procurement has demonstrated initial success in reshaping the composition of the Chinese pharmaceutical market in favor of generics with high quality and low prices.